Enrichment of rotifers (Brachionus plicatilis) with taurine-filled liposomes and taurine-uptake in Ballan wrasse (Labrus bergylta) larvae - Nåvik, Hans Berg (The University of Bergen, 2018)
Taurine has been reported as a conditionally essential nutrient for several marine fish. Ballan wrasse (Labrus bergylta) has become an important species for the Atlantic salmon (Salmo salar) industry in Norway. Rotifers are used as start-feed in the intensive production, however taurine concentration has been shown to be nearly absent in conventionally enriched rotifers. As the Ballan wrasse is adapted zooplankton as feed in their larval stages, the taurine concentration found in zooplankton, which is much higher than in rotifers, is assumed closer to the optimum for Ballan wrasse larvae. Therefore, Ballan wrasse is hypothesized to receive too low taurine levels in intensive production. Liposomes have been used to elevate the concentrations of water-soluble substances, such as taurine in rotifers. Ballan wrasse larvae fed taurine-supplemented rotifers contained significantly higher taurine concentrations than larvae fed both conventionally enriched rotifers, and rotifers enriched with saline water-filled liposomes. This finding indicates that the Ballan wrasse larvae is dependent of taurine through its feed, as they are not likely to be able to biosynthesize taurine in sufficient amounts in vivo. Two experiments were conducted, one investigating the effects of elevated dietary taurine concentration on Ballan wrasse larvae, and a multivariate experiment aimed at investigating the liposome production and enrichment method used in the larval experiment. The larval experiment was affected by production-based difficulties, causing nearly 100 % mortality rates in all tanks, which affected sampling. The larval experiment was concluded at 23 dph, and no significant difference in SL between the treatments were found. Taurine concentration in rotifers fed to the larvae were found to have a significant effect in the taurine concentration in the larval body. Rotifers enriched with taurine had significantly higher taurine concentrations than the control groups. Despite the successful elevation of taurine in the rotifers, the ...